Berberis orthobotrys – A promising herbal anti-tumorigenic candidate for the treatment of pediatric alveolar rhabdomyosarcoma. (30th January 2019) - Adamus, Anna; Peer, Katharina; Ali, Iftikhar; Lisec, Jan; Falodun, Abiodun; Frank, Marcus; Seitz, Guido; Engel, Nadja
Abstract: Ethnopharmacological relevance: Berberis orthobotrys (BORM) is a medical plant with a long history in traditional usage for the treatment of wounds, cancer, gastrointestinal malady and several other diseases. Our previous studies identified the endemic Pakistani plant Berberis orthobotrys Bien. ex Aitch. as promising source for the treatment of breast cancer and osteosarcoma. Aim of the study: The present study was aimed to evaluate the anti-cancer properties of 26 plant derived extracts and compounds including the methanolic root extract of Berberis orthobotrys (BORM) on pediatric alveolar rhabdomyosarcoma (RMA), which is known to develop drug resistance, metastatic invasion and potential tumor progression. Materials and methods: The main anti-tumor activity of BORM was verified by focusing on morphological, cell structural and metabolic alterations via metabolic profiling, cell viability measurements, flow cytometry, western blotting and diverse microscopy-based methods using the human RMA cell line Rh30. Results: Exposure of 25 µg/ml BORM exerts an influence on the cell stability, the degradation of oncosomes as well as the shutdown of the metabolic activity of RMA cells, primarily by downregulation of the energy metabolism. Therefore glycyl-aspartic acid and N-acetyl serine decreased moderately, and uracil increased intracellularly. On healthy, non-transformed muscle cells BORM revealed very low metabolic alterations and nearly no cytotoxic impact. Furthermore, BORM is also capable to reduce Rh30 cell migration ( 50%) and proliferation (induced G2/M cycle arrest) as well as to initiate apoptosis confirmed by reduced Bcl-2, Bax and PCNA expression and induced PARP-1 cleavage. Conclusions: The study provides the first evidence, that BORM treatment is effective against RMA cells with low side effects on healthy cells. Graphical abstract: